Association of Slender Patent Ductus Arteriosus Combined With PFO Related to the Transient Ischemic Attack: A Rare Case Report - Zhi Wen; Mingwu Tian; Zhiqiang Huang; Changxue Wu; Xin Wei (Clinical Case Reports)
ABSTRACT It was a rare case of a 52‐year‐old female with a slender PDA combined with PFO related to a transient ischemic attack that did not improve with aspirin and/or clopidogrel treatment. We closed the PDA using the ADO‐II occluder and closed the PFO with the occluder, resulting in symptom resolution.